QUALITATIVE CHARACTERISTICS OF FINANCIAL REPORTING INFORMATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article has reviewed the importance of international standards in the preparation of financial statements. As a result of the research, the qualitative characteristics of the information in financial statements were identified and proposals were developed to improve the regulatory and legal documents.